Parendodontic Surgery as a Treatment Option: Case Report with One Year Follow-Up - Silva, Jadson Mathyas Domingos da; Silva, Gleidson de Oliveira; Vergetti, Francisco de Assis Crescencio; Costa, Andreza Raianne Oliveira da; Nascimento, Milena Galdino; Almeida Neto, Eduardo Marinho de; Nogueira, Pedro Thalles Bernardo de Carvalho; Vasconcelos, Rafaela Andrade de (ARCHIVES OF HEALTH INVESTIGATION, 2022)
Endodontic treatment aims at eliminating microorganisms from root canal systems. The resistance of these microorganisms contributes for the permanence of the apical lesion, leading to the failure of treatment. The microbiological factor is pointed out as the major cause of failures after intervention. In these cases, root canal retreatment can be performed aims the re-instrumentation, cleaning, and new filling in the root canal. Also, retreatment treatment can be associated with a parendodontic surgery in the attempt to reverse failure without a tooth extraction. The objective of this clinical case is to report a root canal retreatment associated with apical surgery with one year follow-up in the lower central incisor’s region. It was concluded that paraendodontic surgery is an effective and conservative treatment option compared to tooth extractions, and when properly performed, with the aid of good materials such a MTA, brings satisfactory results by returning normal conditions to the periodontal tissue, as well as health and function to the teeth affected by the inflammatory process.